Diterpenoids from the wood of Podocarpus neriifolitus - Sa, Nguyen Hoang; Tam, Nguyen Thanh; Hoang Anh, Nguyen Thi; Thien, Dao Duc; Quan, Tran Duc; Phong, Dinh Thi; Sung, Tran Van; Thuy, Trinh Thi (Vietnam Journal of Chemistry, 2016)
Using combined chromatographic methods, three known diterpenoids, inumakiol D (1), totarol (2) and totarol-19-carboxylic acid (3) along with β-sitosterol and β-sitosterol glucoside were isolated from the ethyl acetate extract of the wood of Podocarpus neriifolius collected in Lam Dong province, Vietnam. Their structures were determined by MS, 1D-, 2D-NMR data analysis and comparison with published references. This is the first report of compounds 1-3 from this plant. Keywords. Podocarpus neriifolius, diterpenoid, inumakiol D, totarol, totarol-19-carboxylic